Strategi Meningkatkan Literasi Keuangan Program Penjamin Simpanan Dan Keputusan Minat Menabung Masyarakat : A Literatur Riview - imam Asyrofi; Fani Monada Essa Putri (Economics and Digital Business Review, 2024)
Saving is an investment in the future. Instilling a savings culture forms a mindset to value money and avoid consumptive behavior. Increasing financial literacy is a crucial thing to do in order to provide knowledge, especially for institutions related to community decisions in saving. The method in this study uses literature literature while the data for this research uses literature studies in the form of books, literature, journals, articles. Research explains that understanding financial literacy affects saving decisions. Knowledge of the risks and benefits of saving increases customer trust and customers trust their assets in institutions under the auspices of the deposit insurance forum (LPS).